Teaching This Class Drives Me Nuts! - Examining the Person and Context Specificity of Teacher Emotions - Frenzel, Anne C.; Becker-Kurz, Betty; Pekrun, Reinhard; Goetz, Thomas (PloS one, 2015)
Teachers' emotions are critically important for the quality of classroom instruction, and they are key components of teachers' psychological well-being. Past research has focused on individual differences between teachers, whereas within-teacher variation across contexts has rarely been considered. As such, the present research addresses the long-standing yet unresolved person-situation debate pertaining to the emotional experiences of teachers. In two diary studies (N = 135, 70% female, and N = 85, 28% female), we examined the role of person, academic subject, and group of students for teacher emotions; focusing on three of the most salient emotions found in teachers: enjoyment, anger, and anxiety. Findings from multi-level analysis confirmed the person specificity of enjoyment, anger, and, in particular, anxiety. In addition, underscoring the existence of within-teacher variability, findings supported that teachers' emotions considerably varied depending on the subject and group of students taught, particularly so for enjoyment and anger. Implications of the person and context specificity of teacher emotions are discussed in relation to assessments and intervention programs aiming to improve teachers' emotional lives in the classroom.